A Study of Corrosion of Root Parts of Metallic Post and Core Reconstructions after their Extraction - Z. Venclíková; J. Fojt; L. Joska (Czech Dental Chamber, 2014)
Introduction and objective: Cast post and cores are an important tool in the reconstruction of a dental crown. This article analyzes the state of cast metallic posts, made of alloys with high silver content, in cases where the restoration failed. Our aim is to point out the risks associated with the use of these alloys. Material and methods: A group of patients, based on a variety of dental indications, to whom it was necessary to extract either teeth with cast post and core or remove cast metallic posts or crowns. Overall, we analyzed 23 prosthetic works that have been exposed to the oral environment for 10 to 29 years, and discuss seven cases with a known history. The state of extracted samples was investigated by scanning electron microscopy and the elemental composition was determined by X-ray energy dispersive analysis (EDS / EDAX). Results and conclusion: The analysis showed that the corrosion problems of cast post and cores relate to the inner wire component as well as cast metallic post. In a situation when the corrosion environment penetrates to the core area, the corrosion process can lead to the formation of bulky iron corrosion products or ions of soluble silver compounds. This results in a strain, which may cause a longitudinal fracture of the tooth root and tissue pigmentation. Since alloys with high silver content are still part of the inventory of dental laboratories and the silver-tin alloy is still offered in the dental market, we felt it nece-ssary to highlight the risk aspects associated with manufacturing root extensions from these materials.